Ctenopharyngodon idella p53 mediates between NF-κB and PKR at the transcriptional level. Issue 69 (October 2017) - Huang, Qingli; Xie, Dingkun; Mao, Huiling; Wang, Haizhou; Wu, Zhen; Huang, Keyi; Wan, Yiqi; Xu, Qun; Hu, Chengyu
Abstract: p53, NF-κB and PKR are well-known to be involved in antiviral response. Although p53 has been reported in fish, its role in the regulation of NF-κB and PKR is not well understood. Here, we cloned and characterized the full length of cDNA sequence of grass carp ( Ctenopharyngodon idella ) p53 ( Ci p53) and its promoter sequence. The full length cDNA of Cip53 was 1879 bp with an ORF of 1116 bp encoding a polypeptide of 371 amino acids. Phylogenetic tree analysis revealed that Ci p53 shares high homology with Dario rerio p53 ( Dr p53). Similar to those of Cip65 and CiPKR, the expression of Cip53 in CIK cells was significantly up-regulated after stimulation with poly I:C. To further understand the roles of fish p53 in the transcriptional control of NF-κB and PKR, Ci p53 and Ci p65 were expressed in E. coli BL21 and purified by affinity chromatography with the Ni-NTA His-Bind resin. In vitro, gel mobility shift assays demonstrated that the high affinity interaction between Ci p65 and Cip53 promoter. Similarly, Ci p53 bound to CiPKR promoter with high affinity. Dual-luciferase reporter assays showed that Ci p65 activated Cip53 promoter and Ci p53 activated CiPKR promoter, respectively. In addition, the role of p53 in p65-p53-PKR transcription pathway was explored. When Cip53 was knockdown in CIK cells, the mRNA levels of Cip65 and CiPKR were decreased. Taken together, p53 may play pivotal roles in transcription pathway of NF-κB and PKR in fish. Highlights: The full-length cDNA and promoter sequence of grass carp p53 were cloned and identified. The expression of Cip53 was significantly up-regulated in CIK cells under the induction of poly I:C. Ci p65 bound to the promoter of Cip53 and Ci p53 bound to the promoter of CiPKR, respectively. Ci p65 played a positive role in Ci p53 transcription and Ci p53 played a positive role in Ci PKR transcription. The decreased mRNA levels of NF-κB and PKR were detected in p53-knockdown CIK cells.